2014
DOI: 10.1088/0954-3899/41/7/075106
|View full text |Cite
|
Sign up to set email alerts
|

Forward–backward multiplicity correlation in high-energy nucleus–nucleus interactions at a few AGeV/c

Abstract: We have presented a systematic study of two-particle rapidity correlations in terms of investigating the dynamical fluctuation observable σ 2 c in the forwardbackward pseudo-rapidity windows by analyzing the experimental data of 16 O-AgBr interactions at 4.5 AGeV/c, 22 Ne-AgBr interactions at 4.1 AGeV/c, 28 Si-AgBr and 32 S-AgBr interactions at 4.5 AGeV/c. The experimental results have been compared with the results obtained from the analysis of event sample simulated (MC-RAND) by generating random numbers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 37 publications
(147 reference statements)
1
35
0
Order By: Relevance
“…Detailed analysis on systematic errors for the same data set has been presented in our earlier publication [48][49]. From our previous papers [48][49], we find that the efficiency of identifying the shower particles contribute to the systematic error of the analysis. We have shown that [48][49] applying the along the track scanning procedure with the help of two independent observers helps us to increase the scanning efficiency to more than 99% and hence to minimize the systematic errors to less than 1%.…”
Section: Discussion Of Systematic Errorsmentioning
confidence: 66%
See 2 more Smart Citations
“…Detailed analysis on systematic errors for the same data set has been presented in our earlier publication [48][49]. From our previous papers [48][49], we find that the efficiency of identifying the shower particles contribute to the systematic error of the analysis. We have shown that [48][49] applying the along the track scanning procedure with the help of two independent observers helps us to increase the scanning efficiency to more than 99% and hence to minimize the systematic errors to less than 1%.…”
Section: Discussion Of Systematic Errorsmentioning
confidence: 66%
“…We have shown that [48][49] applying the along the track scanning procedure with the help of two independent observers helps us to increase the scanning efficiency to more than 99% and hence to minimize the systematic errors to less than 1%. It 11 has been mentioned in [48][49] that along the track scanning method gives reliable event samples because of its high detection efficiency. In nuclear emulsion detector tracks of   e e pair origi ati g fro γ -conversion may cause problem in the identification of pions [48][49].…”
Section: Discussion Of Systematic Errorsmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to collect the data used for the present analysis, stacks of NIKFI-BR2 emulsion pellicles of dimension 20cm 10 cm 600 were irradiated by the 16 O, 28 Si and 32 S beam at 4.5 AGeV/c obtained from the Synchrophasatron at the Joint Institute of Nuclear Research (JINR), Dubna, Russia [78][79][80][81]. According to the Powell [82], in nuclear emulsion detector particles emitted and produced from an interaction are classified into four categories, namely the shower particles, the grey particles, the black particles and the projectile fragments.…”
Section: Methodsmentioning
confidence: 99%
“…To account for the quantum statistics, the hadrons are represented by Gaussian wave packets and effects such as, e.g., Pauli blocking are included in this model. Both UrQMD [29][30][31][32][33][34][35] and DPMJET III [36][37][38] models have been applied successfully to study high-energy collisions.…”
Section: Difference Between Urqmd and Dpmjet III Modelsmentioning
confidence: 99%